Distortion in Interpreting Ahkam Verses: A Case Study of the Hakekok Balakasuta Teachings in Pandeglang Regency: (Distorsi Penafsiran Ayat-ayat Ahkam: Studi Kasus Ajaran Hakekok Balakasuta di Pandeglang) - Nida Roudhotul Hikmah (UIN Kiai Haji Achmad Siddiq Jember, 2025)
The emergence of the Hakekok Balakasuta teaching in Pandeglang Regency, Indonesia, has raised concerns due to its deviation from mainstream Islamic teachings, particularly in the interpretation of ahkam (legal) verses in the Quran. Rooted in the Sunda Wiwitan belief system and founded by Arya in 2021, this spiritual group promotes practices that contradict orthodox Islam, such as altering the shahada (declaration of faith), deeming the five daily prayers non-obligatory, and introducing unconventional rituals, including communal bathing without proper attire, as a form of purification. The primary issues revolve around distorted interpretations of worship practices, including prayer, fasting, zakat (alms), and purification, which misalign with Quranic injunctions and lead to potential religious fragmentation in the community. This study aims to examine the forms of distortion in interpreting ahkam verses within Hakekok Balakasuta teachings and identify the underlying causes. Employing a qualitative descriptive approach rooted in Living Qur'an studies, the research utilized direct observation, in-depth interviews, and documentation as primary data sources from Karangbolong, Pandeglang Regency. Secondary data were drawn from books, journals, tafsirs (Quranic commentaries), and relevant literature. Findings reveal specific distortions, such as viewing prayer as optional rather than obligatory, fasting practices diverging from Islamic norms, and the communal bathing ritual as self-purification, which lacks a scriptural basis. Contributing factors include economic hardships, low educational levels, and insufficient religious awareness among followers. The study highlights the importance of enhancing Islamic education to prevent such deviations and promote accurate Quranic interpretation.